Effect of feeding rumen-escape lipid to postpartum beef heifers - Peters, C.W.; Corah, L.R.; Cochran, R.C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Feeding .25, .5, or 1 lb/d of rumen-escape lipid in a range supplement to beef heifers after calving resulted in increased calf weight gain and milk production at 70 d postpartum compared to control or feeding 2 lb daily. As level of rumen-escape lipid increased, plasma cholesterol and triglycerides also increased when measured after 14 and 28 d of lipid feeding. The interval from parturition to standing estrus generally was longer as level of rumen-escape lipid increased. It appears that intermediate levels (.25, .5, or 1 lb/d) of rumen escape lipid can enhance milk production and calf weight gain; however, the interval to estrus may be prolonged.
Keywords: Beef; Rumen-escape lipid; Beef heifers; Postpartum estrus; Milk; Cholesterol